STRATEGI ORANG TUA DALAM MENDAMPINGI ANAK USIA DINI BELAJAR DARING DI RUMAH - Alit Arta Wiguna Ida Bagus; Ni Luh Drajati Ekaningtyas (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
Early childhood education is a shared responsibility of various parties; not only thegovernment, but also schools, teachers and families (parents). During online learning, learningactivities at home are part of the responsibiliy of the parents. This study aims to determine thestrategies used by parents in accompanying their children during online learning at home. Thisresearch uses descriptive exploration techniques with qualitative analysis. Data collection wascarried out in three different early childhood education institutions (PAUD). The results of the dataanalysis shows that TK A carries out full online learning and uses mentoring strategies by parentsincluding preparing learning equipments, monitoring children during learning, and explainingsubjects that are not understood by the children. PAUD B applies semi-online learning using astrategy: parents take and collect children’s homework every Monday. Meanwhile, PAUD Cimplements offline learning with a mentoring strategy in which the teacher conducts home visits.Parents in PAUD C have a role to supervise their children in learning, where parents come homefrom work and take the time to accompany their children, then advise the teachers to visit theirhomes. In general, it can be concluded that basically parents have no reason to not provide assistanceto their children while learning from home during the COVID-19 pandemic. The synergyy betweenteachers and parents is the essence of a good early childhood education.